2004
DOI: 10.1128/aac.48.3.903-908.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline and Streptomycin Resistance Genes, Transposons, and Plasmids in Salmonella enterica Isolates from Animals in Italy

Abstract: Fifty-eight multidrug-resistant Salmonella enterica strains of 20 serotypes, isolated from animal sources in Italy, were analyzed for tet(A) and strA-strB, conferring tetracycline and streptomycin resistance, respectively. The strA and strB genes were highly prevalent in Salmonella strains of our collection, being detected in 84% of the streptomycin-resistant strains. In many strains, the strA and strB genes were linked to a particular Tn5393-derivative transposon characterized by the presence of the insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 35 publications
9
81
2
4
Order By: Relevance
“…The high rates of tetracycline resistance observed may be related to the transference of several tet genes that confer resistance to Salmonella sp. (Pezzella et al, 2004). Other results presented by Cortez et al (2006), in Brazil, and Wang et al (2013) in China, showed that 86.2% and 78% of the isolated strains, respectively, were also resistant to ampicillin, as also detected in the present study.…”
Section: Resultssupporting
confidence: 75%
“…The high rates of tetracycline resistance observed may be related to the transference of several tet genes that confer resistance to Salmonella sp. (Pezzella et al, 2004). Other results presented by Cortez et al (2006), in Brazil, and Wang et al (2013) in China, showed that 86.2% and 78% of the isolated strains, respectively, were also resistant to ampicillin, as also detected in the present study.…”
Section: Resultssupporting
confidence: 75%
“…Besides the IncI1 plasmids, the bla CTX-M-1 gene was also (52,87). The spread of bla CTX-M-1 -carrying plasmids in animals could be sustained by the use of expanded-spectrum cephalosporins in veterinary medicine.…”
Section: Plasmids Carrying Esbls In Enterobacteriaceae Of Human and Amentioning
confidence: 96%
“…Resistance to streptomycin has been largely documented. Its extensive use, in particular in veterinary medicine, has contributed to the successful spread of resistance genes [33].…”
Section: Discussionmentioning
confidence: 99%